The diasporic Islamic masculinity and the reformulation of European Islam: Theoretical approaches and interpretative perspectives - Fedele, Valentina (Nómadas. Critical Journal of Social and Juridical Sciences, 2015)
Diasporic Islamic hegemonic masculinity is rarely analyzed in both sociology and gender studies, and, if addressed, it is generally linked to phenomena of deviance, not considering the religious as one of the constitutive elements, non-reductionist, but autonomous, of contemporary Islamic masculinity. Based on the issues raised during a doctoral research implemented among diasporic Muslims of North African origin in Italy and France, the article proposes to reverse this perspective, placing the process of construction of diasporic Islamic masculinity in the wider context of the reformulation of European Islam, using a transnational approach and following social-constructivist gender studies. This perspective allows to some highlight elements useful for the understanding of the dynamics underlying the construction of masculinity in contemporary Islamic Mediterranean identifying possible path and directions of recomposition.